Eksplorasi Kegiatan Ekstrakurikuler di MIN 1 Tuban: untuk Meningkatkan Keterampilan dan Minat Bakat Siswa - Prasetyo, Agus Fathoni; Ika Cahyani, Putri; Septia Elly Kumala Asih, Zana; Akmal Zuhriyadi, M. Sahid (Indo-MathEdu Intellectuals Journal, 2025)
Extracurricular activities at school play an important role in developing students' skills and talents outside the classroom environment.This article aims to identify and analyze the experiences of students involved in extracurricular activities at MIN 1 Tuban, as well as their impact on the development of students' skills and talents. The study examines various extracurricular activities such as table tennis, futsal, painting, calligraphy, MTQ (Qur'an recitation), tahfidz (Qur'an memorization), rebana (traditional percussion), marching band, and scouting. The research findings show that these activities not only enhance students’ practical skills but also play a significant role in shaping their interests and talents, such as discipline, responsibility, and the ability to collaborate. With the involvement of supervising or guiding teachers in extracurricular activities, students gain richer and more meaningful learning experiences. This study is expected to contribute to a deeper understanding of the importance of extracurricular activities in the primary education system.